2019
DOI: 10.1136/bmjgh-2018-001308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of community health worker interventions on socioeconomic inequities in maternal and newborn health in low-income and middle-income countries: a mixed-methods systematic review

Abstract: IntroductionCommunity health worker (CHW) interventions are promoted to improve maternal and newborn health in low-income and middle-income countries. We reviewed the evidence on their effectiveness in reducing socioeconomic inequities in maternal and newborn health outcomes, how they achieve these effects, and contextual processes that shape these effects.MethodsWe conducted a mixed-methods systematic review of quantitative and qualitative studies published between 1996 and 2017 in Medline, Embase, Web of Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 55 publications
5
61
0
Order By: Relevance
“…The authors found that home based care practices improved more equitably than care seeking, raising important questions about CHW ability to address health systems challenges. 36 Moreover, CHW programmes can replicate some of the barriers community members face at the clinic level at the community level. For example, a study in Pakistan found that lower caste CHWs were more likely to visit (and to be respected by) their lower caste peers 37 ; Ved et al had similar findings in India.…”
Section: Findings Chw Function and Accountabilitymentioning
confidence: 99%
“…The authors found that home based care practices improved more equitably than care seeking, raising important questions about CHW ability to address health systems challenges. 36 Moreover, CHW programmes can replicate some of the barriers community members face at the clinic level at the community level. For example, a study in Pakistan found that lower caste CHWs were more likely to visit (and to be respected by) their lower caste peers 37 ; Ved et al had similar findings in India.…”
Section: Findings Chw Function and Accountabilitymentioning
confidence: 99%
“…Notable examples are trained community health workers (CHWs) and mother/peer groups for health and nutrition promotion [7][8][9]. Though evidence supports CHW home visits and women's groups for improving maternal and newborn health in low and middle-income countries (LMICs) [10][11][12], evidence from high-quality studies involving such community platforms for delivering nutrition-specific interventions is limited across diverse populations [5]. This is partly…”
Section: Introductionmentioning
confidence: 99%
“…However, this concept receives multiple interpretations in the literature, which are reflected in the use of apparently equivalent terms such as community midwives, lay midwives or TBAs. 30 These terms are often conflated under the broader concept of community health worker, 31 32 which, although it recognises the community roots of traditional midwives, neglects the culture specific roots of their practice. In a similar way, the appellation of lay midwives is used to suggest lack of professional qualification or expert knowledge.…”
Section: Methodsmentioning
confidence: 99%